A Feasibility Study of the Intraductal Administration of Chemotherapy - Love, Susan M.; Zhang, Wei; Gordon, Eva J.; Rao, Jianyu; Yang, Hongying; Li, Junyao; Zhang, Bailin; Wang, Xiang; Chen, Guoji; Zhang, Baoning (Cancer prevention research (Philadelphia, Pa.), 2013)
Preclinical data have shown the potential of the intraductal administration of chemotherapy for breast cancer prevention. Direct translation of this work has been stymied by the anatomical differences between rodents (one duct per teat) and women (5–9 ductal systems per breast). The objective of this phase I study was to show the safety and feasibility of intraductal administration of chemotherapy drugs into multiple ducts within one breast in women awaiting mastectomy for treatment of invasive cancer. Thirty subjects were enrolled in this dose escalation study conducted at a single center in Beijing, China. Under local anesthetic, one of two chemotherapy drugs, carboplatin or pegylated liposomal doxorubicin (PLD), was administered into five to eight ducts at three dose levels. Pharmacokinetic analysis has shown that carboplatin was rapidly absorbed into the bloodstream, whereas PLD, though more erratic, was absorbed after a delay. Pathologic analysis showed marked effects on breast duct epithelium in ducts treated with either drug compared with untreated ducts. The study investigators had no difficulty in identifying or cannulating ducts except in one case with a central cancer with subareolar involvement. This study shows the safety and feasibility of intraductal administration of chemotherapy into multiple ducts for the purpose of breast cancer prevention. This is an important step toward implementation of this strategy as a “chemical mastectomy”, where the potential for carcinogenesis in the ductal epithelium is eliminated pharmacologically, locally, and without the need for surgery. Cancer Prev Res; 6(1); 51–58;. ©2012 AACR.